ANALISIS FAKTOR YANG MEMPENGARUHI PEMBIAYAAN DENGAN MODEL IMPULSE RESPONSE FUCTION (STUDI PT. PEGADAIAN (PERSERO) UPC KERTOSONO) - Astutik, Aprilia Nur; Nurdiwaty, Diah; Faisol, Faisol (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this study was to determine the financing response to changes in interest rates, number of customers, income and services at PT. Pegadaian Kertosono. This study uses the VAR (vector auto regression) method using the STATA 16 program. This study produces a positive response interest rate, when an increase in interest rates has an effect on increasing financing. Then the number of customers produces a negative effect, this shows that when there is a decrease or increase in the number of customers it does not affect financing. Furthermore, income responds positively to financing, meaning that an increase in income will have an impact on increasing financing. After that the service has a negative response to financing, indicating that when there is a decrease or increase in the level of service it does not affect financing.